Comparative Studies of Avian Composition at Ayer Hitam Utara Forest Reserve, Muar, Johor - Tan, Boon Keat; Norazlimi, Nor Atiqah; Mohd Ilham Norhakim Lokman; Abdul Muhaimin Abdul Halim (Enhanced Knowledge in Sciences and Technology, 2024)
The Ayer Hitam Utara Forest Reserve (AHUFR) represents the last peat swamp with diverse habitats in Johor, Malaysia. However, human-induced land conversion poses a threat to the ecological balance, affecting avian species distribution. This study aims to establish an avian species checklist and prioritize conservation areas in AHUFR by comparing different habitats. Sound recording, direct observation, and mist net methods were employed in the peat swamp (north) and lowland forest (south) areas. The sampling revealed 37 species, with 14 in the north and 28 in the south. 27 species were captured by sound recording, 9 species by observation, and 9 species by mist net. Notably, two Vulnerable species were identified: the Rhinoceros hornbill (Buceros rhinoceros) and Great argus (Argusianus argus). T-tests indicated no significant diversity differences between the two areas, but lowland forests showed higher diversity and peat swamp forests exhibited higher evenness. Consequently, the study suggests a slightly higher priority for avian conservation in lowland forests over peat swamp forests in AHUFR.